2023
DOI: 10.3389/fpsyg.2023.1029408
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and problem behaviors in young Chinese children: A moderated mediation model of parenting styles and only children

Abstract: IntroductionThis study tested a moderated mediation model of child number (CN) and parenting styles (PS) in the relationships between family socioeconomic status (SES) and young children’s problem behaviors (PB).MethodsA sample of 1,101 children (Mage = 4.90 years, SD = 1.07) and their parents participated in this study. Parents reported on PS, SES, and children’s PB.Results and DiscussionThe results show SES was positively related to authoritative parenting and negatively related to authoritarian parenting; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Contemporary young Chinese parents are veering toward promoting children’s independence, challenging the traditional norm of grandparents’ indulgence. This change has led to a decline in overly permissive parenting practices ( Scharff, 2022 ; Lin et al, 2023 ; Guo J. et al, 2023 ). Research by Wu (1996) suggests that Chinese parents frequently resort to reprimands to guide their children’s behavior, particularly in academic realms, reflecting an authoritarian approach ( Kriger and Kroes, 1972 ; Lin and Fu, 1990 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary young Chinese parents are veering toward promoting children’s independence, challenging the traditional norm of grandparents’ indulgence. This change has led to a decline in overly permissive parenting practices ( Scharff, 2022 ; Lin et al, 2023 ; Guo J. et al, 2023 ). Research by Wu (1996) suggests that Chinese parents frequently resort to reprimands to guide their children’s behavior, particularly in academic realms, reflecting an authoritarian approach ( Kriger and Kroes, 1972 ; Lin and Fu, 1990 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, parents with low SES tend to lack knowledge and concepts about parenting skills. A previous study among Chinese parents showed that SES was positively related to authoritative parenting (rational and issue-oriented) and negatively related to authoritarian parenting (controlling and punitive) [31]. We also found parents of migrant children had more negative parenting styles (e.g., over-protection, over-interference, favoritism, rejection, and punishment) and less positive parenting styles (e.g., emotional warmth, self-con dence, acceptance, and understanding).…”
Section: Discussionmentioning
confidence: 93%
“…However, persistent disparities in access to educational resources persist in urban and rural areas, across different regions, and social class divisions continue to impede the pursuit of educational equity [46]. Studies illustrated that SES has remained a crucial factor influencing educational equality since China's economic reforms and global integration, and this influence persists despite the increased enrolment in schools [15,47].…”
Section: Context Of the Studymentioning
confidence: 99%